1975
DOI: 10.1080/15287397509529323
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the genetic effects of hycanthone and oxamniquine

Abstract: Oxamniquine (UK-4271; 6-hydroxymethyl-2-isopropylaminomethyl-7-nitro-1,2,3,4-tetrahydroquinoline) is a new schistosomicidal agent currently undergoing clinical investigation in South America. Essentially a complete cure rate against Brazilian Schistosoma mansoni has been seen in adults with a single im dose of 7.5 mg/kg or a single oral dose of 15 mg/kg. These regimens were tolerated without significant toxicity. To assess its mutagenic potential, oxamniquine was examined in a battery of genetic tests designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Furthermore, the alterations of the NDI observed to the compounds 8 and 12 showed that the human cells used responded to the damages induced by the compounds, probably arresting the cell cycle to promote the DNA repair. Unlike these compounds, studies indicate that the oxamniquine has low mutagenic potential (Ray et al 1975), although there are reports of its mutagenic effect when tested on Salmonella typhimurium strain TA100 (Batzinger, Bueding, 1977;Dayan, Deguingand, Truzman, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the alterations of the NDI observed to the compounds 8 and 12 showed that the human cells used responded to the damages induced by the compounds, probably arresting the cell cycle to promote the DNA repair. Unlike these compounds, studies indicate that the oxamniquine has low mutagenic potential (Ray et al 1975), although there are reports of its mutagenic effect when tested on Salmonella typhimurium strain TA100 (Batzinger, Bueding, 1977;Dayan, Deguingand, Truzman, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…Only weak embryotoxicity was detected after applying high oral doses . Studies of mutagenicity were mostly negative, occasionally weakly positive . Side effects were often described to be mild and of short duration.…”
Section: Anthelmintic Drug Therapymentioning
confidence: 99%
“…[100] Studies of mutagenicityw ere mostly negative, occasionally weakly positive. [101][102][103] Side effects were often described to be mild and of short duration.N ausea, dizziness, drowsiness, headache, abdominald iscomfort, vomiting, and diarrhea were most commonly observed. Hallucinations or seizures rarely occurred.…”
Section: Oxamniquinementioning
confidence: 99%
“…More than 3 million people have been treated with OX (Dr. T. Nash, National Institutes of Health; personal communication). It is positive in the Salmonella mutation assay , but it is negative in mammalian cells for SCE induction and chromosomal aberration (Ray et al, 1975), and is noncarcinogenic in animals (Haese and Bueding, 1976).…”
Section: Introductionmentioning
confidence: 99%